2019
DOI: 10.1002/admi.201900684
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic Fabrication of NPN/SiNx Dual Membrane Cavity for Nanopore‐Based DNA Sensing

Abstract: Nanoscale preconfinement of DNA has been shown to reduce the variation of passage times through solid-state nanopores. Preconfinement has been previously achieved by forming a femtoliter-sized cavity capped with a highly porous layer of nanoporous silicon nitride (NPN). This cavity was formed by sealing a NPN nanofilter membrane against a substrate chip using water vapor delamination. Ultimately, this method of fabrication cannot keep a consistent spacing between the This article is protected by copyright. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Figures 1a-c shows the results of a PCR mixture from a commercial kit sensed by a 6 ± 2 nm nanopore in 3.6M LiCl pH 8 at 200 mV (note the uncertainty in the pore size is due to the uncertainty in the effective membrane thickness, likely smaller than the nominal membrane thickness of 10 nm). 36,37 To perform this measurement, a commercial master mix (see Methods section) was added to a sensing salt to mimic the background signals expected of a PCR amplification reaction during nanopore sensing.…”
Section: Nanopore Detection From Commercial Pcr Mixturesmentioning
confidence: 99%
“…Figures 1a-c shows the results of a PCR mixture from a commercial kit sensed by a 6 ± 2 nm nanopore in 3.6M LiCl pH 8 at 200 mV (note the uncertainty in the pore size is due to the uncertainty in the effective membrane thickness, likely smaller than the nominal membrane thickness of 10 nm). 36,37 To perform this measurement, a commercial master mix (see Methods section) was added to a sensing salt to mimic the background signals expected of a PCR amplification reaction during nanopore sensing.…”
Section: Nanopore Detection From Commercial Pcr Mixturesmentioning
confidence: 99%
“…Utilising this advantage, nanopores were fabricated in a SiN x membrane which was separated from a nanoporous membrane by a sub-micron sized cavity. [135][136][137] Using this device structure, it was demonstrated that the conformation of DNA could be controlled by passing the molecules through the nanoporous membrane prior to translocation through the nanopore. This resulted in a narrower distribution of dwell times and in some cases a reduction in the number of folded translocation events, an important result for practical sensing applications.…”
Section: Advantages Of Controlled Breakdownmentioning
confidence: 99%
“…Except for the wet methods of etching, dry etching such as vapor can also react with the selected sacrificial layer and release the nanomembrane. For example, HF vapor was used to remove the SiO 2 layer while Si and graphene layers were well protected [108], and XeF 2 vapor can etch semiconductor layer to release the SiN x and metal multilayer [109,110]. Generally, wet method is a cheap and easy method but easy to corrode the surface of the wanted nanomembrane, while dry method is expensive and complex but with better selectivity of sacrificial layer [111].…”
Section: Patterning and Release Of Nanomembranementioning
confidence: 99%